2005
DOI: 10.1890/04-0957
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Patterns in the Structure of Model and Empirical Food Webs

Abstract: We analyze the properties of model food webs and of fifteen community food webs from a variety of environments -including freshwater, marine-freshwater interfaces and terrestrial environments. We first perform a theoretical analysis of a recently proposed model for food webs-the niche model of Williams and Martinez (2000). We derive analytical expressions for the distributions of species' number of prey, number of predators, and total number of trophic links and find that they follow universal functional forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
282
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(299 citation statements)
references
References 50 publications
9
282
1
1
Order By: Relevance
“…We found that the niche model has an unrealistic distribution of predator numbers per prey species, with a hump at large predator numbers that becomes more pronounced with increasing C or S. This leads to a higher extinction probability with increasing food web complexity. In contrast, empirical data used in this paper and recent studies by other authors (Stouffer et al, 2005) suggest that realistic food web models should have exponential distributions of the numbers of prey and predator species. When we randomized the vulnerability distribution in the niche model, we found positive complexity-stability relations under the condition that Holling type II functional response and f ij = 1/B i is used in the simulations.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…We found that the niche model has an unrealistic distribution of predator numbers per prey species, with a hump at large predator numbers that becomes more pronounced with increasing C or S. This leads to a higher extinction probability with increasing food web complexity. In contrast, empirical data used in this paper and recent studies by other authors (Stouffer et al, 2005) suggest that realistic food web models should have exponential distributions of the numbers of prey and predator species. When we randomized the vulnerability distribution in the niche model, we found positive complexity-stability relations under the condition that Holling type II functional response and f ij = 1/B i is used in the simulations.…”
Section: Resultscontrasting
confidence: 71%
“…The bimodal shape has not been seen either in an analytical evaluation of the vulnerability distribution in the niche model (Stouffer et al, 2005), which was performed in the limit of large species numbers (S ∼ 1000) and a small connectivity z = 2 · L/S = 2 · S · C, (with z 5). For such extreme parameter values (which correspond to a connectance C = 0.005), exponentially decreasing distributions of the numbers of predator and prey species are obtained, which agree well with empirical distributions (which, however typically have connectance values around 0.15, as mentioned before (Dunne et al, 2002)).…”
Section: Niche Modelmentioning
confidence: 99%
“…One major problem lies in the extent to which constituent species are 'lumped' into functional groups, in ways that can bias analysis [55]. Interestingly, Stouffer et al [56] have shown that approximately exponential degree distributions similar to those observed can be derived from at least two apparently different models proposed earlier [57,58]; this finding is reminiscent of much earlier observations that significantly different mechanisms could result in identical distributions of the relative abundance of species.…”
Section: Network Structure and Infectious Disease Dynamicsmentioning
confidence: 85%
“…The niche model matches empirical data much better than the cascade or random models, and a probabilistic version of the niche model is providing ways to further explore the extent to which the constraints imposed by the niche model are consistent with empirical data [32]. These simple models allow exploration of how food-web structure systematically depends on the number of links and species in a system [20].…”
Section: Intervalitymentioning
confidence: 93%
“…A central measure of all networks' structure is the variability of links among nodes or 'degree distributions' that, in food webs, describe the balance among trophic specialists and generalists. When normalized by L/S, degree distributions have a general exponential-type shape [20] indicating that most paths of energy flow through food webs go through relatively few species. This is consistent with species removal experiments in BEF studies, which have suggested a small sub-group of species disproportionately influences productivity [9].…”
Section: Intervalitymentioning
confidence: 99%